Mother Courage and Her Children. - Brecht, Bertolt (Student Editions., 2015)
This Student Edition of Brecht's anti-war masterpiece features an extensive introduction and commentary that includes a plot summary, discussion of the context, themes, characters, style and language as well as questions for further study and notes on words and phrases in the text. It is the perfect edition for students of theatre and literature. In this chronicle of the Thirty Years War of the seventeenth century, Mother Courage follows the armies back and forth across Europe, selling provisions and liquor from her canteen wagon. As the action of the play progresses between the years 1624 and.